Factors influencing the missed nursing care in patients from a private hospital - Hernández Cruz, Raúl; Moreno Monsiváis, María Guadalupe; Cheverría Rivera, Sofía; Díaz Oviedo, Aracely (2017)
Objective: to determine the factors that influence the missed nursing care in hospitalized patients. Methods: descriptive correlational study developed at a private hospital in Mexico. To identify the missed nursing care and related factors, the MISSCARE survey was used, which measures the care missed and associated factors. The care missed and the factors were grouped in global and dimension rates. For the analysis, descriptive statistics, Spearman’s correlation and simple linear regression were used. Approval for the study was obtained from the ethics committee. Results: the participants were 71 nurses from emergency, intensive care and inpatient services. The global missed care index corresponded to M=7.45 (SD=10.74); the highest missed care index was found in the dimension basic care interventions (M=13.02, SD=17.60). The main factor contributing to the care missed was human resources (M=56.13, SD=21.38). The factors related to the care missed were human resources (rs =0.408, p<0.001) and communication (rs =0.418, p<0.001). Conclusions: the nursing care missed is mainly due to the human resource factor; these study findings will permit the strengthening of nursing care continuity. Descriptors: Nursing Care; Patient Care; Human Resources; Communication; Hospitals, Private.